PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA (KBKr) PADA SUB MATERI POKOK ALAT INDRA (Penelitian Quasi Eksperimen pada Siswa Kelas XI SMA Negeri 9 Garut) - Elda Dewi Handayani; Tuti kurniati; Tri wahyu agustina (Department of Biology Education UIN Sunan Gunung Djati Bandung, 2015)
The model of PBL learning is one of alternative way in which can be used to increase the critical thingking skills. The model of PBL learning include, student as participant to so solving problem and for create them as active participant in every solving problem process. In the concept of critical thingking the student aimed to test their ways of solving problem and can aware of mistakes. By using ouasi-experiment design research method and the research itself taking sample in purposive sampling. The population is all of class XI SMAN 9 garut student. The result of research shows that the student’s critical thingking in which the senses material and also with the model of PBL shows the average around 88,51 than KBKr student using PBL model have their without. Score 87,15 the mann whitney test result, we have got Zhitung Ztabel that is 1,0 > 1,66 so that Ha accepted and Ho rejected, and the student response shows that the mod